Status and impact of rural aquaculture practice on Lake Victoria basin wetlands - Waiswa Mwanja, Wilson; Akol, Anne; Abubaker, Laila; Mwanja, Matthew; Msuku, Scot Batman; Bugenyi, Fred (African Journal of Ecology, 2007)
Rural aquaculture in Lake Victoria basin is a fast increasing nontraditional farming activity which if not appropriately practised will lead to degradation of the wetlands. As part of a study to develop appropriate guidelines and model systems for wetlands-based rural aquaculture in the basin a survey was conducted to assess the status and the ecological and socioeconomic impact of rural aquaculture on wetlands and wetlands communities. Aquaculture practice was found to be common but not as a major activity. Aquaculture in the wetlands can be described as a low input-low output production activity and subsistence based on ponds under 400 m2 using free seed from public agencies with hardly any supplementary feeding. Men owned most of the ponds and women only contributed to the management of the fishponds by feeding the fish. Poorly constructed ponds and loss during harvesting have led to the escape of cultured species into the wild. Introduction of nonnative species in the basin has already led to wide ranging ecological, environmental and socioeconomic changes whose impact and usefulness are still very much contentious. Repeat of such scenarios can be avoided if appropriate and science-based models for rural aquaculture farming are developed, tested and disseminated to the communities.
Keywords: Lake Victoria; Rural aquaculture; Wetlands